Translating the Hebrew Bible in Medieval Iberia Oxford, Bodleian Library, MS Hunt. 268 - Alfonso, Esperanza; del Barco, Javier (The Iberian Religious World, 2021)
In Translating the Hebrew Bible in Medieval Iberia Esperanza Alfonso and Javier del Barco offer an edition and comprehensive study of the first Hebrew-vernacular biblical glossary-commentary produced in medieval Iberia that is known to date.